2008
DOI: 10.2165/0002512-200825120-00005
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Medication in Patients with Dementia

Abstract: Measures to facilitate patient medication adherence should be considered an integral part of the comprehensive care of older patients with multiple diseases. However, impairment of cognitive functions and dementia, in particular, may substantially compromise adherence behaviour. Therefore, a literature review was performed to identify factors associated with adherence to medication in patients with cognitive impairment or dementia, and to discuss strategies for improvement of non-adherence. Evidence-based info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(127 citation statements)
references
References 125 publications
2
114
2
2
Order By: Relevance
“…This was demonstrated in a recent study by Bradford et al (2013) of individuals diagnosed with mild to moderate dementia of the Alzheimer's type, suggesting that self-reports from individuals suffering from anxiety are equally as accurate or modestly similar to proxy counterparts (Bradford et al, 2013). Other studies have shown proxy ratings were lower than self-reports of individuals with dementia, resulting in both over and under-estimation biases by the caregivers or proxies (Arlt et al, 2008;Snow et al, 2005). However, words of caution, only trained individuals should administer the measures and researchers should be open to developments of newer instruments incorporating the latest technology.…”
Section: Discussionmentioning
confidence: 85%
“…This was demonstrated in a recent study by Bradford et al (2013) of individuals diagnosed with mild to moderate dementia of the Alzheimer's type, suggesting that self-reports from individuals suffering from anxiety are equally as accurate or modestly similar to proxy counterparts (Bradford et al, 2013). Other studies have shown proxy ratings were lower than self-reports of individuals with dementia, resulting in both over and under-estimation biases by the caregivers or proxies (Arlt et al, 2008;Snow et al, 2005). However, words of caution, only trained individuals should administer the measures and researchers should be open to developments of newer instruments incorporating the latest technology.…”
Section: Discussionmentioning
confidence: 85%
“…External memory aides, such as use of a medication organizer and charts (Park et al, 1992) and tailoring the medication regimen to the individual's daily routine, have been shown to be beneficial in helping people take their medications as prescribed (Insel & Cole, 2005); however, these studies have not directed attention to people with cognitive impairment posthospitalization who may not achieve the same level of benefit without additional cues and other supports. Automated computer-based reminder aides and telephonic reminders may be useful ways to help the person with cognitive impairment (Arlt et al, 2008). It is critical to keep in mind that one size does not fit all, so close monitoring is essential as home healthcare professionals work with patients and/or family members to find the most effective strategies for medication management.…”
Section: Discussionmentioning
confidence: 99%
“…& Medication adherence may also be challenging in those with dementia. Oversight with medications and aids to remind patients to take their medications may be useful in patients with AD dementia [76]. & Other safety precautions include removing harmful objects from the household, including firearms [27].…”
Section: Safety Precautionsmentioning
confidence: 99%